Simulation of ionospheric plasma velocity along the geomagnetic field lines due to the horizontal neutral winds - Grinchenko, S. V.; Dziubanov, D. A.; Ziuzgina, Iu. E. (НТУ "ХПІ", 2014)
With use of horizontal neutral winds model HWM93 there are calculated the elements of a global picture of thermosphere circulation, the changes of value and direction of thermosphere wind over Kharkiv. The calculations of constituent part of vertical component of ionospheric plasma velocity caused by horizontal neutral winds were made.

З використанням моделі горизонтальних нейтральних вітрів HWM93 розраховані елементи глобальної картини термосферной циркуляції, зміни величини і напряму термосферного вітру над Харковом. Проведено розрахунки компоненти вертикальної складової швидкості руху іоносферної плазми, зумовленої горизонтальними нейтральними вітрами.
Keywords: horizontal wind model HWM93; dynamics of an ionosphere; ionospheric plasma velocity; ionosphere; модель горизонтальних нейтральних вітрів HWM93; динаміка іоносфери; швидкість руху; іоносферна плазма; іоносфера